Biofouling resistance of boron-doped diamond neural stimulation electrodes is superior to titanium nitride electrodes in vivo. (22nd August 2016) - Meijs, S; Alcaide, M; Sørensen, C; McDonald, M; Sørensen, S; Rechendorff, K; Gerhardt, A; Nesladek, M; Rijkhoff, N J M; Pennisi, C P
Abstract: Objective. The goal of this study was to assess the electrochemical properties of boron-doped diamond (BDD) electrodes in relation to conventional titanium nitride (TiN) electrodes through in vitro and in vivo measurements. Approach . Electrochemical impedance spectroscopy, cyclic voltammetry and voltage transient (VT) measurements were performed in vitro after immersion in a 5% albumin solution and in vivo after subcutaneous implantation in rats for 6 weeks. Main results . In contrast to the TiN electrodes, the capacitance of the BDD electrodes was not significantly reduced in albumin solution. Furthermore, BDD electrodes displayed a decrease in the VTs and an increase in the pulsing capacitances immediately upon implantation, which remained stable throughout the whole implantation period, whereas the opposite was the case for the TiN electrodes. Significance. These results reveal that BDD electrodes possess a superior biofouling resistance, which provides significantly stable electrochemical properties both in protein solution as well as in vivo compared to TiN electrodes.